Implantes cocleares: Desarrollo y perspectivas - Martínez Rams, E. A.; Cano Ortiz, S. D.; Garcerán Hernández, V. (Revista Mexicana de Ingenieria Biomedica, 2006)
The development and implementation of Cochlear Implant devices have lead to a useful alternative for partial re-establishment of profoundly deaf people. The Cochlear Implant has been highly concerned with the combined efforts of the scientists from several areas as bioengineering, speech recognition, medicine and signal processing. This paper pretends to make an updated review about the novel technology used in cochlear prosthesis as well as the perspectives and tendencies of this knowledge area.